Synthesis of Heterocyclic [8]Circulenes and Related Structures - Hensel, Thomas; Andersen, Nicolaj N.; Plesner, Malene; Pittelkow, Michael (Synlett, 2016)
In this account we give an overview of the synthesis and properties of heterocyclic [8]circulenes. Much of the interest in studying heterocyclic [8]circulenes stems from the planar cyclooctatetraene core often contained in these compounds, which in principle is antiaromatic. We start with a short introduction to the hydrocarbon [n]circulenes and proceed to describe the synthetic chemistry involved in creating tetraoxa[8]circulenes, with particular focus on the acid-mediated oligomerization of benzo- or naphthoquinones, resulting in some simple rules for predicting the outcome of the oligomerization reactions. These rules have guided the synthetic strategies for the preparation of azatrioxa[8]circulenes and diazadioxa[8]circulenes, which will be described in separate sections of this account. More traditional synthetic strategies have been applied in the preparation of octathia[8]circulene, tetrathiatetraselena[8]circulene, and a number of other heterocyclic [8]circulenes, and these synthetic efforts will be highlighted. Finally, a section describing structures that are closely related to the heterocyclic [8]circulenes will be presented, and at the end we will comment on the extensive theoretical work regarding the question of aromaticity/antiaromaticity of the central cyclooctatetraene of heterocyclic[8]circulenes.1 Introduction2 Synthesis of [n]circulenes2.1 [4]Circulene2.2 [5]Circulene2.3 [6]Circulene2.4 [7]Circulene2.5 [8]Circulene3 Synthesis of Tetraoxa[8]circulenes: A Historical Perspective4 Synthesis of Azatrioxa[8]circulenes5 Synthesis of Diazadioxa[8]circulenes6 Synthesis of Other Heterocyclic [8]Circulenes7 Synthesis of Structurally Related Compounds8 Hetero[8]circulenes and Related Compounds as Tools to Study Aromaticity and Antiaromaticity9 Conclusion and Outlook
Keywords: circulenes; heterocycles; aromaticity; antiaromatcity; synthesis; geometry; cyclooctatetraenes; nucleus-independent shifts